Pengaruh Variasi Massa Campuran Sampah Plastik Jenis Low Density Polyethylene (LDPE) Dan Poly Propylene (PP) Terhadap Volume Produk Cair Proses Pirolisis - Sadhu, Putu Gangga Prabawa; Suarnadwipa, I Nengah; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstractt In this research a pyrolysis process was carried out for Low Density Polyethylene (LDPE) plastic waste in the form of plastic bags and Poly Propylene (PP) in the form of plastic food packaging with the aim of overcoming the negative impacts of plastic waste. The test varied the mass of the mixture of LDPE and PP plastic waste at a mass ratio percentage of 75% PP plastic to the total mass of the mixture, 50% PP plastic to the total mass of the mixture, and 25% PP plastic to the total mass of the mixture. The higher the mass percentage of PP plastic to the total mass of the mixture will increase the volume of the liquid product produced Keywords : Pyrolysis, LDPE, PP, mixture of LDPE and PP plastic waste, liquid product volume